White Fat Progenitors Reside in the Adipose Vasculature - Tang, Wei (2008)
White adipose (fat) tissues regulate metabolism, reproduction and lifespan. Adipocytes form throughout life, with the most marked expansion of the lineage occurring during the postnatal period. Adipocytes develop in coordination with the vasculature, but the identity and location of white adipocyte progenitor cells are unknown. We used genetically marked mice to isolate proliferating and renewing adipogenic progenitors. We find that most adipocytes descend from a pool of these proliferating progenitors that are already committed either prenatally or early in postnatal life. These progenitors reside in the mural cell compartment of the adipose vasculature but not in the vasculature of other tissues. Thus, the adipose vasculature appears to function as a progenitor niche and may provide signals for adipocyte development.